Acute haematological and bilirubin responses to stress of sprint and endurance runs - Agbonjinmi, A. P.; Adodo, S.; Abari, G. S.; Adeogun, J. O. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
This study was designed to investigate the following two hypotheses: (a) Neither sprint nor endurance run would have any significant effect on haematological variables of haemoglobin (Hb), packed cell volume (PCV) and red cell count (RCC); (b) neither sprint nor endurance run would have any significant effect on serium bilirubin. Results: In the male subjects sprint run provoked a nonsignificant increase in Hb, PCV, RCC, Btotal and Bcon while Buncon did not change. In the female subjects sprint run resulted in nonsignificant decrease in Hb, PCV, RCC and Bcon; Btotal and Buncon revealed nonsignificant increase. 2.4 Km run resulted in nonsignificant decrease in Hb, PCV, RCC and nonsignificant increase in Btotal and Bcon in male subjects. 2.4 Km run resuled in significant decrease in PCV (p ? 0.10) in female subjects. Hb, RCC and Bcon were nonsignificantly reduced while Btotal and Buncon were nonsignificantly increased in the female subjects. When the data were pooled, 2.4 Km run resulted in borderline significant reduction in PCV (p ? 0.05). 400m run did not produce any change in Buncon in male subjects while 2.4 Km run resulted in decrease in Buncon. There was no difference in Buncon responses to 400m and 2.4 Km runs in female subjects. These results did not produce the evidence to support that exercise haemolysis is the cause of sports anaemia. We accepted the two hypotheses in respect of the variables under study with the exception of PCV. These results confirmed our previous findings on sports anaemia [3]. We recommend, for further study in this area, red blood survival studies using Cr51 labelled red blood cells.